Isolated Synchronous Splenic Metastasis from Endometrial Carcinoma: Case Report - Atike Pinar Erdoğan; Hanife Seda Mavili; Mustafa Şahbazlar; Gonca Akdere Ateş; Mehmet Gürdal Savsar; Nagihan Kolkıran (Düzce Tıp Fakültesi Dergisi)
Endometrial carcinoma is the most prevalent malignancy of the female reproductive system. However, splenic metastasis remains an infrequent occurrence due to the spleen's distinct anatomical and microenvironmental characteristics. This case report described a 66-year-old female patient diagnosed with endometrial carcinoma, who underwent total hysterectomy, bilateral salpingo-oophorectomy, pelvic peritonectomy, omentectomy, and splenectomy following the intraoperative detection of splenic metastasis. The histopathological evaluation confirmed high-grade serous carcinoma with a Ki-67 proliferation index of 90%, as well as metastatic involvement of the ovaries, peritoneum, and spleen. The patient subsequently received adjuvant carboplatin-paclitaxel chemotherapy, radiotherapy, and multiple-step systemic therapy due to disease progression. No significant adverse effects were observed in multi-step chemotherapy. The present case demonstrates the diagnostic challenges and treatment strategies encountered in a rare occurrence of endometrial carcinoma with splenic metastasis.